Experimental Analysis of Thermal Runaway and Propagation in Lithium-Ion Battery Modules. Issue 9 (1st January 2015) - Lopez, Carlos F.; Jeevarajan, Judith A.; Mukherjee, Partha P.
Abstract : While the energy and power density of lithium-ion batteries (LIBs) are steadily improving, thermal safety continues to remain a critical challenge. Under abuse conditions, exothermic reactions may lead to the release of heat that can trigger subsequent unsafe reactions. The situation worsens in a module configuration, as the released heat from an abused cell can activate a chain of reactions in the neighboring cells, causing catastrophic thermal runaway. This work focuses on experimental elucidation and analysis of different LIB module configurations to characterize the thermal behavior and determine safe practices. The abuse test consists of a heat-to-vent setting where a single cell in a module is triggered into thermal runaway via a heating element. The cell-to-cell thermal runaway propagation behavior has been characterized. Results have shown that increasing the inter-cell spacing in a module containing cylindrical cells significantly decreases the probability of thermal runaway propagation. Additionally, it was determined that appropriate tab configuration combined with cell form factors exhibit a major influence on thermal runaway propagation. Different thermal insulation materials have been analyzed to determine their ability to ameliorate and/or potentially mitigate propagation effects.